THE UNITY OF FUNDAMENTAL AND APPLIED KNOWLEDGE AND HIGH TECHNOLOGY - Броннікова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The article deals with the problems of modern post-non-classical science of the beginning of the XXIst century. New demands of society determine changes in the functioning of science, in the production and consumption of knowledge. In particular, the priority in our time is given to applied research, which is “closer” to technology. Fundamental science suffers from criticism, neglect, and underfunding. At the same time, it is absolutely obvious that without the achievements of fundamental science there would be no success in applied research and technology would not be improved. For example, for all areas of nanotechnology a common source is such a fundamental science as quantum mechanics. The aim of the article is to clarify how the interaction takes place between fundamental and applied research, on the one hand, and between these types of research and high technology. Research methods of this study are philosophical and general scientific methods, as well as systemic and synergistic approaches. Discussion. In the extensive literature devoted to the problems of the relationship between fundamental applied and fundamental applied to high technologies, it is noted that there are no universal models of their interaction. Research results.The specificity of a particular study and the secrets of creativity cannot be schematized and formalized. Conclusions. As a result, the popular problem of the interrelation of the fundamental-applied and the newest technologies proves the unity of the theory and practice of scientific activity. At the same time, tremendous progress in the creation of high technologies indicates that a new scientific paradigm is being formed.